Consumption Insurance and Household Vulnerability: Evidence from Thailand - Wongmonta, Sasiwooth (SOUTHEAST ASIAN JOURNAL OF ECONOMICS, 2019)
An assessment of risk and vulnerability provides insight into how risk affects household’s well-being and the effectiveness of coping strategies. This paper uses the 2005, 2007, 2010, and 2012 panel data sets from Socioeconomic Survey (SES) of Thailand to investigate the extent of consumption insurance and household vulnerability across socioeconomic groups. The results are supportive of partial insurance. Consumption appears to be better insured in rural areas than urban areas. Empirical estimates indicate that households with educated heads and living in an owned house are more resilient to shocks. In contrast, households with self-employed heads, infants and small children, engaging in farm activities, and female heads are more vulnerable groups. Furthermore, idiosyncratic health shocks had no significant effect on vulnerability. Household’s coping strategies including savings, borrowing, and remittances help protect them from economic shocks. Thailand’s formal safety nets also contribute to reducing vulnerability except for the public pension payment.